PERBAIKAN PERTUMBUHAN BIBIT KELAPA SAWIT YANG MENGALAMI CEKAMAN GENANGAN AIR SECARA PERIODIK DENGAN PEMBERIAN PUPUK DAUN DAN GIBERELIN - Fajar Nopendri; Nurbaiti Nurbaiti; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The present study aims to improve the growth of palm oil seedling periodically covered with puddle by giving foliar fertilizer and gibberellin. The research was experimentally conducted at an experimental garden of Faculty of Agriculture, Riau University, Pekanbaru from August until December 2017 using completely random split plot design under 3 replications. The main plot is foliar fertilizer concentration (D) consisting of d0 = non foliar fertilized (0 ppm), d1 = foliar fertilized 1,500 ppm, d2 = foliar fertilized 3,000 ppm and the sub plot was gibberellin concentration (G) consisting of g0 = no gibberellin (0 ppm), g1 = gibberellin 15,000 ppm, g2 = gibberellin 30,000 ppm. The observed consists of: seedling height, total leaf midribs, bar diameter, total adventive roots, roots volume, shoot root ratio, dry seedling weight and seedling quality index. The data were analyzed using analysis of variance and orthogonal contrast tests at a level of 5%. The results that dry weight and quality index of palm oil seedling which are periodically covered with puddle are affected by an interaction between foliar fertilizer and gibberellin, while height seedling and dry seedling weight are affected by gibberellin concentration. The height of palm oil seedling which are periodically covered with puddle can be improved use by gibberellin. The weight of dry seedling can be improved through giving foliar fertilizers with gibberellin, provided that the concentrated are both equal. The improvement of seedling quality index with foliar fertilizer is determined by the gibberellin concentration given. Keywords: Palm oil seedling, periodic coverage of the puddle, foliar fertilizer and gibberellin